2023
DOI: 10.1002/ptr.7795
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of the cellular antioxidant pool contributes to resveratrol‐induced senescence and apoptosis in lung cancer

Abstract: Resveratrol (RES) has various pharmacological bioactivities and its anticancer effects in lung cancer have been proven. However, the underlying mechanisms of action of RES in lung cancer remain unclear. This study focused on Nrf2-mediated antioxidant systems in RES-treated lung cancer cells. A549 and H1299 cells were treated with various concentrations of RES at different times. RES decreased cell viability, inhibited cell proliferation, and increased the number of senescent and apoptotic cells in a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…If we consider the whole population, senescence and apoptosis are not contradictory. For example, Liang et al found that resveratrol promotes lung cancer cell apoptosis and induces cellular oxidative stress with accompanying senescence phenotypes (Liang et al, 2023). In our view, the coexistence of RGC apoptosis and aging is a key factor in causing visual nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…If we consider the whole population, senescence and apoptosis are not contradictory. For example, Liang et al found that resveratrol promotes lung cancer cell apoptosis and induces cellular oxidative stress with accompanying senescence phenotypes (Liang et al, 2023). In our view, the coexistence of RGC apoptosis and aging is a key factor in causing visual nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer potential of resveratrol was also investigated against lung cancer lines A549 and H1299 in a study by Liang et al (2023) [17]. The authors observed a remarkable decrease in cell viability for A549 and H1299 cells at concentrations of 50 µM and 25 µM, respectively, after 24 h. However, in 48 h, cell viability was significantly inhibited by about 50% at 25 µM for H1299 and A549 cells.…”
Section: Resveratrolmentioning
confidence: 99%
“…This bioactive compound has an antioxidant action resulting in several health benefits. Furthermore, research shows that resveratrol also has antimicrobial and antifungal activity [ 34 ] and can be used in the treatment of various diseases, including cancer [ 14 , 17 ].…”
Section: Overview Of Polyphenols and Their Anticancer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol (RSV) is a natural polyphenol abundant in various berries and foods 5 . It has diverse biological activities such as antitumor 6 , anti-inflammatory 7 , anti– cardiovascular disease 8 , and antioxidant effects 9 . RSV exhibits a significant effect on gut microbiota.…”
Section: Introductionmentioning
confidence: 99%